2012
DOI: 10.1016/j.jtcvs.2011.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pressure load caused by right ventricular outflow tract obstruction on right ventricular volume overload in patients with repaired tetralogy of Fallot

Abstract: Our study demonstrated that the RV pressure load prevented RV dilatation from chronic PR without systolic dysfunction. It is suggested that a proper relief of RVOT obstruction with acceptable residual stenosis is more advantageous than aggressive RVOT enlargement in the long-term outcome of repaired TOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 23 publications
9
33
1
Order By: Relevance
“…Rather, patients with AP tend to have residual RVOT obstruction more frequently than patients with TAP, which may lead to less frequent PVI by preventing RV dilatation [8,26]. Therefore, the decision of PVI was made not merely by the presence of severe pulmonary regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, patients with AP tend to have residual RVOT obstruction more frequently than patients with TAP, which may lead to less frequent PVI by preventing RV dilatation [8,26]. Therefore, the decision of PVI was made not merely by the presence of severe pulmonary regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…That an element of residual RVOT obstruction may protect against late RV dilatation is suggested by Yoo et al, 31 who used CMR to assess 190 patients with repaired ToF and found that patients with residual RVOT obstruction (mean gradient, 34.2±10.0 mm Hg) had less RV volume overload and no medium-term deterioration of RV function compared with those with predominant pulmonary regurgitation. Van der Hulst and colleagues 32 also demonstrated that mild residual pulmonary stenosis reduced the need for PVR in 171 patients with ToF repair over a follow-up of 24 years.…”
Section: Discussionmentioning
confidence: 96%
“…Previously, surgeons used smaller TAPs and infundibular incisions to limit free regurgitation of the PV. These measures indeed slowed the effect of PI on the RV, 14 but this mere delay in RV dysfunction led eventually to a fate similar to that of patients who developed isolated PI after the TAP. 15 The more fruitful solution, as we have outlined it above, relieves the RVOT stenosis as well as possible and creates a competent PV in patients who really need a TAP.…”
Section: Discussionmentioning
confidence: 98%